Exploration and Identification of Medicinal Plants in The Kesuma Bangsa Herbal Garden Lampung - Windiyani, Intan Poespita; Khoirunisa, Sally (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Medicinal plants are plants that contain a substance that is used as one of the ingredients for treatment. The use of medicines derived from plants or natural sources is more common because it is cheaper and has fewer side effects. Identification of medicinal plants in the Kesuma Bangsa Herbal Garden was carried out with the aim of finding out the types of medicinal plants and parts of the plants used as medicine to treat diseases. The method used in this study was a descriptive method with a sampling technique using an exploratory technique where researchers made direct observations and then collected data by recording and photographing using a camera. The results showed that there were 20 species from 18 plant families that were used and processed as traditional medicines, where the types of medicinal plants that were commonly found were from the Araceae and Euphorbiaceae families. The leaf part with a percentage of 40% was the most widely used as traditional medicine.